2003
DOI: 10.2105/ajph.93.11.1871
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Latino Adolescents’ Adherence to Treatment for Latent Tuberculosis Infection: A Controlled Trial

Abstract: Coaching can increase Latino adolescents' adherence to treatment for latent tuberculosis infection and should contribute to tuberculosis control for adolescents at high risk of contracting the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 58 publications
3
72
0
Order By: Relevance
“…In 10 studies, the main intervention delivery site was the patient's usual clinic [38,39,[42][43][44][47][48][49]51,54]. Alternative delivery sites, used alone or in addition to the clinic, included the patients' homes [41,43,45,46,50], schools [52], and in four cases, various venues including community facilities were considered [40,41,43,46].…”
Section: Intervention Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…In 10 studies, the main intervention delivery site was the patient's usual clinic [38,39,[42][43][44][47][48][49]51,54]. Alternative delivery sites, used alone or in addition to the clinic, included the patients' homes [41,43,45,46,50], schools [52], and in four cases, various venues including community facilities were considered [40,41,43,46].…”
Section: Intervention Deliverymentioning
confidence: 99%
“…Alternative delivery sites, used alone or in addition to the clinic, included the patients' homes [41,43,45,46,50], schools [52], and in four cases, various venues including community facilities were considered [40,41,43,46]. One intervention was based on text messaging [53].…”
Section: Intervention Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Hovell et al 62 Dick et al 42 Subtotal Subtotal Demissie et al 67 Alvarez-Gordillo et al 66 Case-control Barnwell et al 38 Intervention White et al 58 Chaisson et al 52 Morisky et al 56 Subtotal …”
Section: Cohortmentioning
confidence: 99%
“…137 Strategies that have increased adherence to treatment for latent tuberculosis infection in immigrant and refugee populations include patient reminders (calendar stickers for self-monitoring, phone calls, letters and directly observed therapy), adherence coaches who speak the same language as the patient, ongoing education of patients and providers, and cultural case management. 25,[144][145][146] Goldberg and colleagues found that when case managers were matched to the ethnic and linguistic background of patients and provided treatment for latent tuberculosis and monitoring during monthly home visits, adherence with treatment was substantially improved (82% v. 37%), as compared with standard clinic-based management before the intervention.…”
mentioning
confidence: 99%